PENGARUH KESEIMBANGAN KEHIDUPAN KERJA, STRES KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI PT. GEO GIVEN VISI MANDIRI SIDOARJO - Cecilia Vira; Johannes Silalahi (Cahaya Ilmu Bangsa, 2024)
This research aims to analyze whether work-life balance, work stress and work environment influence employee performance at PT. Geo Given Visi Mandiri Sidoarjo both partially and simultaneously. This research was conducted on employees at PT. Geo Given Vision Mandiri Sidoarjo. With a total sample of 90 respondents collected using a questionnaire and the analysis techniques used were Validity Test, Reliability Test and Multiple Linear Regression with SPSS 27, and also Hypothesis Testing. The results of this research: Work-life balance, work stress and work environment simultaneously have a significant effect on employee performance at PT. Geo Given Visi Mandiri Sidoarjo, work-life balance partially has a significant effect on work on employee performance at PT. Geo Given Visi Mandiri Sidoarjo, Work stress partially has a significant effect on work performance at PT. Geo Given Visi Mandiri Sidoarjo, Work Environment partially has a significant influence on work performance at PT. Geo Given Vision Mandiri Sidoarjo.